2015
DOI: 10.1007/978-3-319-18660-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Finite Energy Coordinates and Vector Analysis on Fractals

Abstract: Abstract. We consider (locally) energy finite coordinates associated with a strongly local regular Dirichlet form on a metric measure space. We give coordinate formulas for substitutes of tangent spaces, for gradient and divergence operators and for the infinitesimal generator. As examples we discuss Euclidean spaces, Riemannian local charts, domains on the Heisenberg group and the measurable Riemannian geometry on the Sierpinski gasket.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Completing 1 a (X )/ ker • H with respect to • H we obtain a Hilbert space H, we refer to it as the space of generalized L 2 -vector fields associated with (E, F ). This is a version of a construction introduced in [17,18] and studied in [13,[49][50][51][52][53]55,77], see also the related sources [20,29,30,99]. The basic idea is much older, see for instance [15,Exercise 5.9], it dates back to ideas of Mokobodzki and LeJan.…”
Section: Resistance Forms and First Order Calculusmentioning
confidence: 99%
See 1 more Smart Citation
“…Completing 1 a (X )/ ker • H with respect to • H we obtain a Hilbert space H, we refer to it as the space of generalized L 2 -vector fields associated with (E, F ). This is a version of a construction introduced in [17,18] and studied in [13,[49][50][51][52][53]55,77], see also the related sources [20,29,30,99]. The basic idea is much older, see for instance [15,Exercise 5.9], it dates back to ideas of Mokobodzki and LeJan.…”
Section: Resistance Forms and First Order Calculusmentioning
confidence: 99%
“…A discussion of more general diffusion coefficients a should involve suitable coordinates, see [40,53,96]. In view of the fact that natural local energy forms on p.c.f.…”
Section: Remark 37mentioning
confidence: 99%
“…There have been interests in the understanding of gradients of functions and non-linear partial differential equations on fractals with non-linearities involving first-order derivatives (see e.g. [16, 1820, 33] and references therein). A new class of semi-linear parabolic equations involving singular measures on the Sierpinski gasket was proposed and studied in [27], where, among other things, a Feynman–Kac representation was obtained assuming the existence of weak solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper is a part of a broader program that aims to connect research on derivatives on fractals ( [8,9,[13][14][15][25][26][27][28]31,33,35,[37][38][39][40][41]46,51,54] and references therein) and on more general regular Dirichlet spaces [29,30,34] with classical and geometric analysis on metric measure spaces ( [6,10,12,[21][22][23][24][42][43][44][45]50] and references therein). In our previous article [36] we showed that on certain topologically one-dimensional spaces with a strongly local regular Dirichlet form one can prove a natural version of the Hodge theorem for 1-forms defined in 2 -sense: the set of harmonic 1-forms is dense in the orthogonal complement of the exact 1-forms.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the reader can consult the papers [7,10,[42][43][44][45] and references therein. Our current paper is a step in a long-term program (see [29][30][31][32][33][34][35][36][37][38]) to develop parts of differential geometry and their applications to mathematical physics (see [3][4][5]) for spaces that carry diffusion processes but no other smooth structure. Our approach is somewhat complementary to the celebrated works [12,21,22] because, although our spaces are metrizable, we do not use any particular metric in an essential way, and we do not use functional inequalities.…”
Section: Introductionmentioning
confidence: 99%